Web-based survey on injuries among ultimate frisbee athletes in Japanese college sports: sex differences in injury location and onset - Yuki Muramoto; Takeshi Kimura; Akira Kinoda; Yuichi Yamada; Yoshinori Katsumata; Kazuki Sato (BMC, 2024)
Abstract Background Ultimate Frisbee (Ultimate) has gained significant popularity. However, a comprehensive understanding of injury characteristics, including sex differences in injury location and onset, remains unclear. This study aimed to investigate the injury profile of male and female athletes using data from the Japanese University Athletic Association survey. Methods Data were collected through a web-based survey conducted between June and October 2022, focusing on injuries sustained within the past year. Athletes provided detailed information, including injury location, severity, and onset pattern. This study utilized data collected through the UNIVAS survey, offering insights into the injury landscape among female Ultimate athletes. The study examined factors influencing lower limb injuries, including training days and the nature of contact during play. Results A total of 116 athletes participated in the survey with 57 (49.1%) reporting injuries, of which 42 injuries involved the lower limbs. Lower-extremity injuries exhibited a higher likelihood of occurrence in female compared to male athletes (p = 0.05, φ = 0.18). Athletes with lower limb injuries demonstrated significantly more training days (p = 0.01, Cohen's d = 0.76). Non-contact injuries were more prevalent than contact injuries (p < 0.01, φ = 0.53), with non-contact injuries often causing prolonged interruptions in competition. Conclusions Female Ultimate athletes experienced a high frequency of severe lower extremity injuries, particularly those stemming from non-contact incidents. More training days were an independent factor associated with these outcomes.